2021
DOI: 10.2196/25235
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Digital Intervention to Support Shared Decision-making in Children’s and Young People’s Mental Health: Mixed Methods Pilot Randomized Controlled Trial

Abstract: Background Interventions to involve parents in decisions regarding children’s and young people’s mental health are associated with positive outcomes. However, appropriately planning effectiveness studies is critical to ensure that meaningful evidence is collected. It is important to conduct pilot studies to evaluate the feasibility and acceptability of the intervention itself and the feasibility of the protocol to test effectiveness. Objective This pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…China’s internet hospitals are a new medical mode that has developed rapidly in the past 5 years. Previous studies, such as those regarding Carolinas Asthma Coach [ 12 ], the AFib app [ 13 ], e-Quit worRx [ 14 ], Power Up [ 15 ], and iBdecide [ 16 ], focused on the application of doctor-patient SDM through a disease or a disease management software. To date, no doctor-patient SDM app has been used in an internet hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…China’s internet hospitals are a new medical mode that has developed rapidly in the past 5 years. Previous studies, such as those regarding Carolinas Asthma Coach [ 12 ], the AFib app [ 13 ], e-Quit worRx [ 14 ], Power Up [ 15 ], and iBdecide [ 16 ], focused on the application of doctor-patient SDM through a disease or a disease management software. To date, no doctor-patient SDM app has been used in an internet hospital.…”
Section: Discussionmentioning
confidence: 99%
“…e-Quit worRx is used in the treatment plan decision-making for patients in a smoking cessation program [ 14 ]. Power Up is used to record the mental status of adolescents and supports SDM during adolescent mental treatment [ 15 ]. iBdecide is a web-based tool used for adolescents on ulcerative colitis treatment, and this tool promotes patients’ active participation in doctor-patient communication [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the MRC framework, the intervention then entered the pilot and feasibility phase for testing the intervention, as discussed in the study protocol [ 56 ]. Preliminary results of the feasibility study [ 57 ] indicated that the intervention itself is generally acceptable by parents, carers, and health care professionals. The findings also indicate that there is scope for further development of Power Up for Parents.…”
Section: Discussionmentioning
confidence: 99%